'It is all about getting the volumes down'. Organizational framings of risk in relation to waste, waste management and temporality. Issue 2 (1st February 2020) - Olofsson, Jennie
Abstract: Drawing on an ethnographic fieldwork at a waste facility site in the northern parts of Sweden, this article investigates organizational framings of risk (Hutter and Power 2005 ) in relation to waste and practices of waste management, employing the concept of temporality. The suggestion is that organizational framings of risk, as it contributes to steering the risk perception of the employees, also cater to a particular temporal register. In relation to the purposes of this article, the risks that my informants mentioned and/or perceived – as part of a particular organizational framework – were most often seen in terms of situated inconveniences and hazards that required technical, and logistic solutions. While this enabled them to take action, it also contributed to bounding risk and risk perception to a particular temporal register, intimately linked to what Barbara Adam (1998 ) refers to as the logics of industrial time. The logics of industrial time also suffuse formulations of current environmental policies and waste management plans, on a national as well as on an EU level where waste is seen primarily as a resource that continuously needs to be invented anew. As such, the logics of industrial time follow closely the beat of market fluctuations. Talking to representatives for the current waste facility site and observing some of their daily activities, potential risks with waste and practices of waste management were often weighed against other factors such as effectiveness, swiftness, and economic profits or losses: factors that also corresponded to short-time temporalities. While this reasoning, at first seemed to outperform any notion of risk, it actually conformed to the risks acknowledged by the organizational setting of which my informants were part.